A Bibliometric Literature Review Analysis of Public Sentiment Towards the Implementation of ETLE Cameras at Intersection Four - Hidayat, Agung Nur; Luthfiansyah, Fahmi Nabhan; Maulana, Sevan Alif; Toruan, Erni Sari Lumban; Taufik, Mohamad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The implementation of the Electronic Traffic Law Enforcement (ETLE) system at the Kadipaten intersection in Majalengka is a strategic step to improve traffic order through electronic camera-based surveillance. This study aims to evaluate public sentiment toward ETLE technology using a bibliometric approach and keyword visualization analysis. The Bibliometric method was used to collect and analyze 1,000 publications from Google Scholar, with the assistance of the Publish or Perish and VOSviewer software. The results indicate that the majority of studies highlight the important role of cameras in improving traffic efficiency and road safety. Keywords such as video camera, traffic camera, speed camera, and radar frequently appear, reflecting the high level of attention given to sensor technology and traffic monitoring. Keyword network visualization also reveals a strong connection between driver behavior, road design, and the effectiveness of ETLE cameras. This study provides recommendations to improve public acceptance through education, outreach, and the development of inclusive and transparent policies.